2001
DOI: 10.1016/s0895-7061(00)01275-9
|View full text |Cite
|
Sign up to set email alerts
|

Family history of hypertension and left ventricular mass in youth: possible mediating parameters

Abstract: Whether positive family history (FH) of essential hypertension (EH) in normotensive youth is associated with increased left ventricular mass (LVM) and hemodynamic, anthropometric, and demographic parameters previously associated with increased LVM in adults is unknown. To examine these issues, 323 healthy youth (mean age, 13.6 +/- 1.3 years), 194 with positive FH of EH (61% African Americans, 39% whites) and 129 with negative FH of EH (33% African Americans, 67% whites) were evaluated. Hemodynamics were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…14 LVM was calculated using the necropsy-validated formula of Devereux et al 21 Intra-and interrater coefficients of variation for all cardiac structures assessed were Ͻ10%. 22 Because we were interested in LVM growth as a function of age, we did not adjust LVM for body size (height 2.7 or body surface area [BSA]). We do report these mean values for each ethnic/gender group at first visit in Table 1, however, to enable comparison with values in the literature.…”
Section: Procedures and Measurementsmentioning
confidence: 99%
“…14 LVM was calculated using the necropsy-validated formula of Devereux et al 21 Intra-and interrater coefficients of variation for all cardiac structures assessed were Ͻ10%. 22 Because we were interested in LVM growth as a function of age, we did not adjust LVM for body size (height 2.7 or body surface area [BSA]). We do report these mean values for each ethnic/gender group at first visit in Table 1, however, to enable comparison with values in the literature.…”
Section: Procedures and Measurementsmentioning
confidence: 99%
“…Besides effects on the neurological system, many other studies have reported arousal and physiological reactions in video game playing, Reported effects include increases in breath duration in children (Denot-Ledunois et al, 1998) and increases in cardiovascular reactivity, blood pressure (most often systolic blood pressure), and oxygen consumption in children or adolescents (Modesti et al, 1994), as well as in adults of all ages (Segal and Dietz, 1991;Mounier-Vehier et al, 1995), especially in those with a family history of hypertension (Ditto and Miller, 1989;Cook et al, 2001) and in those with Type A personality (i.e., competitive individuals; Griffiths and Dancaster, 1995). Cardiovascular reactivity to video games in young men has also been taken as a reliable predictor of the future occurrence of hypertension (Markovitz et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the finding of dopamine release during video game playing (which involved learning to navigate a tank for a monetary incentive) suggests that, as in the case of animals, this neurotransmitter may play a role in the anticipatory or appetitive phase of motivated behavior in humans (Koepp et al, 1998). Based on these findings, video games have often been used in studies as a stressor to measure cardiovascular reactivity (e.g., Modesti et al, 1994;Cook et al, 2001). Yet, secretion of the stress-related hormone per se, namely cortisol, has rarely been measured.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that PVR is higher in young subjects with than without FHT. 48 FHT is known to be a major risk factor in the development of essential hypertension. 49,50 The results of the present study also suggested that PVR was elevated in the subjects with high BP0 and/or FHT.…”
Section: Clinical Application Of the Fop Measurementmentioning
confidence: 99%